BOHATER W SERWISACH INFORMACYJNYCH NA PRZYKŁADZIE „AKTUALNOŚCI” TELEWIZJI KATOWICE OD MOMENTU UTWORZENIA STACJI POD WSPÓŁCZESNOŚĆ - Fudala-Barańska, Aleksandra (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
For 50 years, the TV news respond to basic questions: who, what, where, when, why and how? Information services, however, despite of many technical changes, graphics and execution comply with the requirements of information as a species. There was no heroes, rarely appeared in a television news more than one statement. Everything changed after 1997, when TVN, later TVN 24 and finally TVP INFO had sprung up a media scene. These stations were modeled on the US CNN’s Ted Turner. New requirements for the implementation of television material, based on the assemblies to be “close to the people,” and “the center of events” very quickly established themselves in regional newspapers, implementing information for antennas nationwide. This article, on the example of the “Aktualności” – the information service of Television Katowice, shows the transformation of information, characterized by emotions, emotions, where the “hero” plays a key role.